Comparative Analysis of Perceived Service Quality among Prolanis Participants in Urban and Rural Primary Health Centers in the Malang Region - Ika Cahyaningrum; Arifen Leihu Pajojang; Karolus Sandiwan Canggang (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Non-communicable diseases (NCDs), particularly hypertension and diabetes mellitus, remain a significant public health problem in Indonesia. The Chronic Disease Management Program (Prolanis) was developed to improve participants’ health status through continuous care at Primary Health Care (PHC). The quality of care is one of the factors influencing participants’ perceptions of Prolanis services. However, differences in regional characteristics, social conditions, and resource availability between urban and rural community health centers (Puskesmas) have the potential to influence participants’ perceptions of service quality. Therefore, this study aims to analyze differences in Prolanis participants’ perceptions of service quality between urban and rural Puskesmas in the Malang region. This study employed a comparative design with a cross-sectional approach, conducted at one urban community health center and one rural community health center. The study sample consisted of 145 Prolanis participants (73 from the urban community health center and 72 from the rural community health center), selected using consecutive sampling (adjust to the correct method if consecutive sampling was not used). The research instrument used the SERVQUAL questionnaire, which covers five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using the Mann–Whitney test because the data distribution was not normal. The results of the study indicate that there is a difference in perceptions of service quality between Prolanis participants at urban and rural community health centers (p<0.001; effect size (r)=0.58). Participants at rural community health centers had a higher perception of service quality compared to participants in urban areas. Significant differences were found in the dimensions of tangibles, responsiveness, assurance, and empathy, while the reliability dimension did not show any significant differences.